International comparison of Shari’ah governance guidelines: AAOIFI, IFSB and BNM - Kasim, Nawal; Htay, Sheila Nu Nu; Syed, Ahmed Salman (2013)
Issue of the corporate governance has emerged with the birth of the corporation. However, it became an attractive issue due to the financial crisis. Similarly, the issue of Shari’ah compliance in Islamic finance is given the attention when the Islamic finance industry arose. Therefore, renowned international organizations such as Accounting, Auditing Organization for Islamic Financial Institutions (AAOIFI) and Islamic Financial Services Board (IFSB) have provided the Shari’ah governance guidelines. In addition, Bank Negara Malaysia (BNM) has laid down the similar guideline. However, to our knowledge, there is no research has been conducted in comparing these guidelines. In our opinion, it is necessary to compare them in order to find out whether there is any variation among the suggestions given by the guidelines. Therefore, the purpose of this paper is to make a comparison among these Shari’ah governance guidelines and to propose the most comprehensive elements to be included in the Shari’ah governance guideline. It has been found that Shari’ah governance framework provided by AAOIFI has seven sections which discussed the Shari’ah Supervisory Board, Shari’ah review, Internal Shari’ah review, audit and governance committee, statement on governance principles corporate social responsibility conduct and disclosure. In the case of IFSB, the framework includes scope and approach of Shari’ah governance system, how to use the framework and the qualitative characteristics of Shari’ah Supervisory Committee. BNM provides the general requirements of the framework and qualitative characteristics which are similar to the IFSB and in addition, it also provides the guidelines on Shari’ah review and Shari’ah audit which are also similar to AAOIFI. BNM further provides the guideline on the functions of Shari’ah risk management and Shari’ah research in Islamic finance.